Lung injury in uncomplicated and severe falciparum malaria: a longitudinal study in papua, Indonesia. - Maguire, G; Handojo, T; Pain, M; Kenangalem, E; Price, R; Tjitra, E; Anstey, N (2005)
BACKGROUND: In patients with severe malaria, acute respiratory distress syndrome usually develops after the start of drug treatment and is a major cause of death. Its pathogenesis is not well understood. METHODS: Respiratory symptom, spirometry, and gas transfer analyses were performed longitudinally in adults in Papua, Indonesia, with uncomplicated (n=50) and severe (n=30) falciparum malaria; normal values were derived from 109 control subjects. Gas transfer was partitioned into its alveolar-capillary membrane (D(M)) and pulmonary vascular (Vc) components, to characterize the site of impaired gas transfer. RESULTS: Cough was frequent in both patients with uncomplicated malaria (50%) and those with severe malaria (30%) and resolved by day 14. Reduced midexpiratory flow indicated obstruction of the small airways. Gas transfer was significantly impaired in patients with severe malaria. D(M) was reduced in patients with severe malaria but not in those with uncomplicated malaria and only returned to normal levels after 2 weeks. In patients with uncomplicated malaria, Vc was reduced at presentation but improved thereafter. In patients with severe malaria, Vc decreased with treatment and was lowest at day 7. CONCLUSIONS: Our results suggest that pulmonary vascular occlusion occurs in both patients with uncomplicated malaria and those with severe malaria, likely from sequestration of both red blood cells (RBCs) and white blood cells. There was also impaired alveolar-capillary membrane function in patients with severe malaria but not in those with uncomplicated malaria. Persistent impairment long after clearance of parasitized RBCs suggests prolonged posttreatment inflammatory alveolar-capillary injury.